Perancangan Sistem Informasi Manajemen Aset Laboratorium Berdasarkan Pendekatan Human Centered Design (HCD) - Zaki Nugraha Muhammad; Allsela Meiriza; Pacu Putra; Nabila Rizky Oktadini; Putri Eka Sevtiyuni (STMIK Budi Darma, 2023)
In the current era, information technology has become increasingly crucial in almost every aspect of work, both within organizations, communities, and industries. The Panca Bhakti Bandar Lampung STIKes laboratory supports students in carrying out practical activities that require them to use specific tools and materials for the lab work. However, the absence of a technology to assist in the borrowing of lab equipment and materials has posed challenges for both the laboratory staff and students. Therefore, a laboratory asset management information system is needed to help laboratory staff in managing data, especially asset borrowing data, and to assist students in requesting lab asset borrowing for their practical needs. The research method will be based on the Human-Centered Design (HCD) approach with Inspiration, Ideation, and Implementation phases. The design result in the form of a prototype will be tested using the System Usability Scale (SUS) questionnaire method to determine whether the laboratory asset management information system design is suitable for use or not. Based on the SUS score of 78.5, which falls under the excellent category, it can be concluded that the application design is suitable for use